Education and Ethics of IbnMiskaweh: Presentation and Analysis of His Book ""Ethics Perfection and Ethnic Purification - Adnan A. Al-Farraji (Sultan Qaboos University, 2014)
Having read the book titled "Ethics Perfection and Ethnic Purification" authored by IbnMiskaweh with its contents on education and ethics, I wish to present the contents of this book to benefit from the ideas and opinions of IbnMiskaweh in our current societies. I have written this article emerging from the biography of the author, his scientific status, his books and essays, some of his decencies and advices. Then I talked about the importance of this book and its content, analyzing its texts, showing as much as possible of the educational and ethical principles included therein which we think satisfy our desired goal for highlighting the role of this scholar in the field of education and ethics.